Glutamate kinase as a potential biomarker of heavy metal stress in plants - Pavlíková, Daniela; Pavlík, Milan; Staszková, Ludmila; Motyka, Václav; Száková, Jirina; Tlustos, Pavel; Balík, Jirí (Ecotoxicology and environmental safety, 2008)
Changes of glutamate kinase activity (GKA) in plants under cadmium and zinc chronic stress reported here reveal a regulatory role of this enzyme in plant heavy metal stress adaptation and indicate its potential use as a stress biomarker. Results of the first experimental series confirmed the toxic effects of cadmium and zinc at tested levels (30, 60, 90 mg Cd kg(-1) and 250, 500, 750 mg Zn kg(-1) soil) for spinach. A significant decrease of GKA in plants grown on contaminated treatments was found. Changes of GKA of plants grown on the highest contaminated treatments in the second series of experiments showed a similar course as a curve of plant stress response indicating the process of plant adaptation to chronic stresses--the decline of GKA in period of damage of cell activities, increase of its activity in period of maximum resistance and its following decrease in period of the plant metabolism depletion.
Keywords: nadzemní části rostlin; Soil Pollutants; Adaptation, Physiological; biologické markery; Zinc; kadmium; fosfotransferasy s karboxylovou skupinou jako akceptorem; Phosphotransferases (Carboxyl Group Acceptor); Biomarkers; látky znečišťující půdu; zinek; Plant Components, Aerial; Spinacia oleracea; fyziologická adaptace; Cadmium